2011
DOI: 10.1080/00221309.2011.582525
|View full text |Cite
|
Sign up to set email alerts
|

Object Naming in Dyslexic Children: More Than a Phonological Deficit

Abstract: ABSTRACT. In the present study, the authors investigate how some visual factors related to early stages of visual-object naming modulate naming performance in dyslexia. The performance of dyslexic children was compared with 2 control groups-normal readers matched for age and normal readers matched for reading level-while performing a discrete naming task in which color and dimensionality of the visually presented objects were manipulated. The results showed that 2-dimensional naming performance improved for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…Some indirect evidence seems consistent with the hypothesis of a contribution of low-level visual factors to RAN performance and its association with reading (Stainthorp et al, 2010; Araújo et al, 2011a). Using a visual naming task Araújo et al (2011a) manipulated some variables related to early stages of visual processing of objects and found that, in contrast to control readers, naming performance of DD subjects did not improve with color or 3-dimensional object presentation compared with black-and-white or 2-dimensional object presentation respectively. These results lead the authors to state that “ processes involved in early visual feature analysis or in the integration of visual information stored in long-term memory might be affected in dyslexia ” (p. 224).…”
Section: Introductionsupporting
confidence: 69%
“…Some indirect evidence seems consistent with the hypothesis of a contribution of low-level visual factors to RAN performance and its association with reading (Stainthorp et al, 2010; Araújo et al, 2011a). Using a visual naming task Araújo et al (2011a) manipulated some variables related to early stages of visual processing of objects and found that, in contrast to control readers, naming performance of DD subjects did not improve with color or 3-dimensional object presentation compared with black-and-white or 2-dimensional object presentation respectively. These results lead the authors to state that “ processes involved in early visual feature analysis or in the integration of visual information stored in long-term memory might be affected in dyslexia ” (p. 224).…”
Section: Introductionsupporting
confidence: 69%
“…Based on previous behavioral (e.g., Jones et al, 2010) and ERP studies (Eddy and Holcomb, 2010;Eddy et al, 2006), we expected shorter response latencies and also attenuated (less negative) amplitudes of the N/P190 and N300 visual components for those target pictures that were preceded by a picture prime relating on the perceptual dimension (compared to unrelated primetarget pairs), while perceptual priming effects on the N400 ERP component are not strongly predicted. We note here that previous behavioral reports had already alluded to the contribution of early stages of processing on the naming performance in dyslexia (i.e., prior to higher level of linguistic processing; e.g., Araújo et al, 2011a;Jones et al, 2008Jones et al, , 2010, and one of the exciting aspects of using ERPs is that we can tackle the specific processes alluded to in this assumption (early versus late visual processing stages).…”
Section: The Current Studymentioning
confidence: 99%
“…This is a quite interesting result as it suggests for the first time that individuals with dyslexia may fail to activate an intermediate representation that relies on a "more complex" integration of perceptual features onto form-specific representations in memory, reflected in the N300 neural marker. Some previous behavioral studies had already explored for the possible involvement of early stages prior to higher level linguistic processing in dyslexia, by using a manipulated version of a naming task (e.g., Araújo et al, 2011a;Jones et al, 2008Jones et al, , 2010. For example, Araújo and colleagues manipulated various surface attributes that should affect stimulus discriminability and visual feature analysis (such as the amount of detail/complexity and color), fundamental to successful recognition.…”
Section: Perceptual Relationshipmentioning
confidence: 99%
See 2 more Smart Citations